Impact of Hemoglobin Level, White Blood Cell Count, Renal Dysfunction, and Staphylococcus as the Causative Organism on Prediction of In-Hospital Mortality from Infective Endocarditis: A Single-Center Retrospective Cohort Study - Koike, Masamichi; Doi, Takahiro; Morishita, Koki; Uruno, Kosuke; Kawasaki-Nabuchi, Mirei; Komuro, Kaoru; Iwano, Hiroyuki; Naraoka, Syuichi; Nagahara, Daigo; Yuda, Satoshi (International Heart Journal, 2024)
Infective endocarditis (IE) is a highly fatal disease in cases of delayed diagnosis and treatment, although its incidence is low. However, there have been few single-center studies in which the risk of in-hospital death from IE was stratified according to laboratory findings on admission and the organism responsible for IE. In this study, a total of 162 patients who were admitted to our hospital during the period from 2009 to 2021, who were suspected of having IE according to the modified Duke classification, and for whom IE was confirmed by transesophageal echocardiography were retrospectively analyzed. Patients were observed for a mean-period of 43.7 days with the primary endpoint being in-hospital death. The in-hospital death group had a lower level of hemoglobin (Hb), higher white blood cell (WBC) count, lower level of estimated glomerular filtration rate (eGFR), and higher frequency of Staphylococcus being the causative agent than those in the non-in-hospital death group. In overall multivariate analysis, Hb, WBC count, eGFR, and Staphylococcus as the causative agent were identified to be significant prognostic determinants. IE patients with Hb < 10.6 g/dL, WBC count > 1.4 × 104/μL, eGFR < 28.1 mL/minute/1.7 m2, and Staphylococcus as the causative agent had significantly and synergistically increased in-hospital death rates compared to those in other IE patients. Low level of Hb, high WBC count, low eGFR, and Staphylococcus as the causative agent of IE were independent predictors of in-hospital mortality, suggesting that these 4 parameters may be combined to additively stratify the risk of in-hospital mortality.